Organosilanesulfonic acid-functionalized Zr-TMS catalysts: synthesis, characterization and catalytic applications in condensation reactions - Chidambaram, M.; Venkatesan, C.; Singh, A. P. (Applied Catalysis A-General, 2006)
Organosilanesulfonic acid (-Si-R3S-R4SO3H, OSA)-functionalized mesoporous Zr-TMS (Zr-TMS-Si-R3S-R4SO3H, Zr-TMS-OSA) was synthesized either by post-synthetic modification of Zr-TMS (zirconia-based transition metal oxide mesoporous molecular sieves) with 3-mercaptopropyltrimethoxysilane (3-MPTS) and further with 1,4-butanesultone (1,4-BS) or by in situ one-pot synthesis procedure. A number of physico-chemical characterization techniques have been used to show that the organosilanesulfonic acid groups were anchored on to the walls of Zr-TMS. MCM-41-Si-R3S-R4SO3H-20 (MCM-41-OSA-20) was also prepared by post-synthesis procedure for comparison. Physico-chemical properties of in situ made A-Zr-OSA-20, Zr-TMS-SO3H-20 and MCM-41-OSA-20 were compared with Zr-TMS-OSA catalysts. The catalytic activity of the materials was tested in liquid phase condensation of aniline with p-formaldehyde to 4,4'-diaminodiphenylmethane (4,4'-DADPM). Results showed that Zr-TMS-OSA catalysts were more active than Zr-TMS-SO3H-20, MCM-41-OSA-20 and A-Zr-OSA-20 and more selective than Zr-TMS-SO3H-20 and A-Zr-OSA-20 catalysts. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Acid catalyst; condensation of aniline; mesoporous ZrO2; organic functionalization; organosilanesulfonic acid

Oxidation of ethyl benzene and diphenyl methane over ordered mesoporous M-MCM-41 (M = Ti, V, Cr): synthesis, characterization and structure-activity correlations - Jha, Ratnesh Kumar; Shylesh, S.; Bhoware, Shrikant S.; Singh, A. P. (Microporous and Mesoporous Materials, 2006)
Transition metals (M = Ti, V, Cr) were incorporated into the MCM-41 framework by surfactant-assisted direct hydrothermal (DHT) methods and were characterized in detail by XRD, N-2 adsorption-desorption, TG-DTG/DTA, SEM/TEM, DR UV-Vis, XPS and EPR. The structural regularity as well as the textural properties of the M-MCM-41 materials was confirmed by XRD, TEM and adsorption-desorption techniques. Nature of metal species and the percentage of framework as well as extra framework metal sites in the MCM-41 matrix are discussed in detail by various spectroscopic techniques. The catalytic activity as well as the selectivity of the M-MCM-41 catalysts were explored in the one-step liquid-phase oxidation reaction of ethyl benzene and diphenyl methane. Reaction data showed that the oxidation activity is more when H2O2 was used an oxidant, acetonitrile as solvent and V-MCM-41 as catalyst. However, the selectivity towards the desired keto derivatives (ethyl benzene to acetophenone and diphenyl methane to benzophenone) follows the order, Ti-MCM-41 > V-MCM-41 > Cr-MCM-41. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: diphenyl methane; Ethyl benzene; MCM-41; Oxidation

One step synthesis of chromium-containing periodic mesoporous organosilicas and their catalytic activity in the oxidation of cyclohexane - Shylesh, S.; Srilakshmi, Ch.; Singh, A. P.; Anderson, B. G. (Microporous and Mesoporous Materials, 2007)
Chromium-containing ethane-bridged hybrid mesoporous materials (Cr-PMO) with uniform hexagonal arrangement were synthesized by two different synthesis routes using 1,2-bis(triethoxysilyl)ethane (BTEE) and tetraethyl orthosilicate (TEOS) as silica sources and alkyltrimethyl ammonium salts (ATMA) as surfactants. Powder X-ray diffraction, TEM, N-2 adsorption-desorption, FT-IR, in situ FT-Raman, UV-ViS, XPS, Si-29 MAS NMR and C-13 CP MAS NMR were used to probe the mesoporous structure and the nature of chromium sites in the hybrid catalyst matrix. PXRD, TEM and N-2 adsorption-desorption analysis showed that the original hexagonal structure of the materials is maintained after chromium substitution, while FT-Raman, UV-Vis and XPS analysis showed that chromium atoms exist in a highly dispersed state. The catalytic performance of the chromium-containing hybrid samples was tested in the liquid-phase oxidation of cyclohexane with aqueous hydrogen peroxide (H2O2) and non-aqueous tert-butylhydroperoxide (TBHP) as oxidants. The hybrid materials exhibited better catalytic activities and were more stable than the conventional Cr-MCM-41 catalyst. The higher catalytic activity of the new chromium-containing molecular sieves is attributed to the improved hydrophobicity of the materials and to the complementary structural features that facilitates the accessibility of cyclohexane to the active framework chromium sites. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Cr-MCM-41; Cr-PMO; Cyclohexane; hybrid mesoporous materials; Oxidation

Organofunctionalization of vanadium(III) acetylacetonate complex over aminofunctionalized SBA-15 for sulfoxidation reactions - Lazar, Anish; Sanjush, K. S.; Singh, A. P. (Advanced Porous Materials, 2016)
Recyclable SBA-15 supported aminopropyl vanadium(III) acetylacetonate heterogeneous catalyst has been synthesized by covalent anchoring of vanadium(III) acetylacetonate over aminofunctionalized SBA-15 via. post grafting method, V(III)(acac)3NH2@SBA-15. The synthesized catalyst was characterized by elemental analysis, ICP-OES, XRD, N2 sorption analysis, FT-IR, 29Si NMR spectroscopy, XPS, SEM and TEM. The percentage of nitrogen and vanadium in V(III)(acac)3NH2@SBA-15 was determined by elemental analysis and ICP-OES, respectively. XRD and N2 sorption analyses provide the information about the structural integrity (Mesoporous structure) and textural properties of all synthesized catalysts. The presence and degree of organofunctionalization on SBA-15 were monitored by FT-IR and 29Si NMR spectroscopy, respectively. Moreover, the oxidation state and the chemical environment of vanadium metal in V(III)(acac)3NH2@SBA-15 were revealed by XPS spectroscopy. Eventually, the morphology and topographic information of the synthesized catalysts were confirmed by SEM and TEM imaging. The synthesized catalyst was evaluated in oxidation of various sulfides and the results show that V(III)(acac)3NH2@SBA-15 catalyst exhibits higher conversion and selectivity towards the sulfoxidation reaction compared to the neat V(III)(acac)3 complex and blank reaction. The synthesized catalyst was recycled four times.